2019
DOI: 10.1007/s10826-019-01438-0
|View full text |Cite|
|
Sign up to set email alerts
|

Experiences of Having a Parent with Serious Mental Illness: An Interpretive Meta-Synthesis of Qualitative Literature

Abstract: Objectives Previous research found that burdens are put on relatives to patients with serious mental illness. A majority of the studies have described the situation of being a husband/wife or parent of someone who is mentally ill. However, little is known about the perspective of childhood experiences and the effect on adult life from having a parent with mental illness. Hence, the purpose of this review was to investigate experiences of having a parent with serious mental illness. Methods We used a qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 39 publications
3
39
0
Order By: Relevance
“…47 Conversely, measures of family history also mediate environmental effects such as higher rates of birth and pregnancy complications, 48–50 growing up in an unfavorable home environment, 51 out-of-home placement, 52 elevated divorce rate, alterations in parental communication, 53 altered school functioning, 54 and the psychosocial impact of growing up with a parent with mental illness. 55 What the results do indicate, however, is that current transdiagnostic measures of polygenic risk lack impact in epidemiological general population studies, beyond very small but statistically significant associations. Genetic factors may contribute to variance of mental health in population-based samples, but it appears that they are not captured by the current version of various transdiagnostic PRS.…”
Section: Discussionmentioning
confidence: 96%
“…47 Conversely, measures of family history also mediate environmental effects such as higher rates of birth and pregnancy complications, 48–50 growing up in an unfavorable home environment, 51 out-of-home placement, 52 elevated divorce rate, alterations in parental communication, 53 altered school functioning, 54 and the psychosocial impact of growing up with a parent with mental illness. 55 What the results do indicate, however, is that current transdiagnostic measures of polygenic risk lack impact in epidemiological general population studies, beyond very small but statistically significant associations. Genetic factors may contribute to variance of mental health in population-based samples, but it appears that they are not captured by the current version of various transdiagnostic PRS.…”
Section: Discussionmentioning
confidence: 96%
“…This is likely in part explained by the fact that particularly parental family history also reflects environmental influences, such as higher rates of birth and pregnancy complications 230,231 , growing up in an unfavorable home environment 232 , out-of-home placement 233 , elevated divorce rate, alterations in parental communication 234 , and poor school performance 235 . The sizeable impact of growing up with a parent with severe mental illness on psychological and social development has been recently reviewed 236 . Therefore, a positive family history should be accompanied by an examination of the devel-opmental impact of parental psychopathology and the clinical needs associated with this.…”
Section: Family Historymentioning
confidence: 99%
“…Family history is also of direct clinical relevance, as the first episode of primary psychosis typically occurs when patients are still dependent on and/or living with their parents. The presence of parental psychopathology may indicate reduced family resilience and increased need for family support 236 .…”
Section: Family Historymentioning
confidence: 99%
“…Painful experiences linger in the adult children, resulting in ambivalent, strained and confusing relationships (Foster, 2010; Murphy et al., 2011; O'Connell, 2008). In a meta-synthesis aimed at investigating adult life with a severely mentally ill parent, Källquist and Salzman-Erikson (2019) documented that feelings, thoughts, relationships, personal growth, health and wellbeing were affected. The findings of this meta-synthesis underline what was previously reported; adverse emotions during childhood, such as fear of mentally ill parents hurting themselves and mistrust related to their unpredictable behaviour, remain in adult life (Mechling, 2016; Murphy et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, adult children have been documented to feel invisible to health and social service providers (Maunu and Stein, 2010). A tendency to conceal the mental illness socially adds to long-standing feelings of shame and embarrassment (Källquist and Salzmann-Erikson, 2019; Murphy et al., 2017). All the same, adult children have reported that, on parents' good days, their childhood was filled with hope, joy and care.…”
Section: Introductionmentioning
confidence: 99%